The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/0269216319858247
|View full text |Cite
|
Sign up to set email alerts
|

Patient and carer involvement in palliative care research: An integrative qualitative evidence synthesis review

Abstract: Background: Patient/carer involvement in palliative care research has been reported as complex, difficult and less advanced compared to other areas of health and social care research. There is seemingly limited evidence on impact and effectiveness. Aim: To examine the evidence regarding patient/carer involvement in palliative care research and identify the facilitators, barriers, impacts and gaps in the evidence base. Design: Qualitative evidence synthesis using an integrative review approach and thematic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
89
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(98 citation statements)
references
References 107 publications
(345 reference statements)
6
89
0
3
Order By: Relevance
“…The barriers and facilitators to partnering with frail and/ or seriously ill patients (e.g., funding, infrastructure, role clarity, capacity building for both patients and researchers, structural inclusivity, trust and willingness to collaborate) are similar to those reported in other systematic and scoping reviews of patient engagement [2,12,22,28,[75][76][77]. When engaging frail and/or seriously ill patients as partners across the research cycle, the degree of illness and/or frailty, and potential instability in patients' health warrants more concern for [7, 45, 47, 51, 53-55, 62, 63, 69, 70] 11 (37%) Emotional/peer support [7, 51, 53, 55, 57, 62-64, 66, 69, 70] 5 (17%) Emotional vulnerability or emotional distress [7,47,55,71,72] 10 (33%) Incorporation of patients' priorities for research and outcomes [7,24,50,51,54,56,57,61,65,67] 8 (27%) Develop new knowledge and skills [45,51,55,59,60,62,63,71] 5 (17%) Physical/cognitive fatigue [7,47,53,55,72] 3 (10%) Acquire insights into disease and treatment [51,55,69] Researcher -Perceived Impacts…”
Section: Discussionsupporting
confidence: 55%
“…The barriers and facilitators to partnering with frail and/ or seriously ill patients (e.g., funding, infrastructure, role clarity, capacity building for both patients and researchers, structural inclusivity, trust and willingness to collaborate) are similar to those reported in other systematic and scoping reviews of patient engagement [2,12,22,28,[75][76][77]. When engaging frail and/or seriously ill patients as partners across the research cycle, the degree of illness and/or frailty, and potential instability in patients' health warrants more concern for [7, 45, 47, 51, 53-55, 62, 63, 69, 70] 11 (37%) Emotional/peer support [7, 51, 53, 55, 57, 62-64, 66, 69, 70] 5 (17%) Emotional vulnerability or emotional distress [7,47,55,71,72] 10 (33%) Incorporation of patients' priorities for research and outcomes [7,24,50,51,54,56,57,61,65,67] 8 (27%) Develop new knowledge and skills [45,51,55,59,60,62,63,71] 5 (17%) Physical/cognitive fatigue [7,47,53,55,72] 3 (10%) Acquire insights into disease and treatment [51,55,69] Researcher -Perceived Impacts…”
Section: Discussionsupporting
confidence: 55%
“…Similar to other studies, our findings showed the importance of the broad principle of flexibility to facilitate involvement. 11,[24][25][26] In palliative care, providing flexible methods of involvement (e.g. in-person, online) was seen to be essential to successfully collaborate with individuals living in complex and unpredictable circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…10 A recent review identified eight broad themes which facilitated and hindered successful involvement within this field. 11 These included definitions and roles, values and principles, organisations and culture, training and support, networking and groups, perspectives and diversity, relationships and communication, and emotions and impact. 11 However, most involvement in palliative care research to date has been consultative, rather than co-productive, and many of the approaches which have been evaluated have focused only on cancer-specific populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palliative care research participation: Research involving people who are terminally ill is difficult due to the perceived vulnerability of the population and professional caution. 40 Professional gatekeeping is a challenge, 64 and biased samples consisting of patients who are mostly well or particularly motivated is often problematic. However there is ample evidence that many terminally ill patients are interested in taking part in research and may benefit from doing so.…”
Section: Stakeholder Evidence Gapsmentioning
confidence: 99%